Operationalize ML by empowering people (Data Science Salon, 2019)
"Presented by, Jeff Sharpe, Manager/Master Software Engineer at Capital One and Niraj Tank, Sr. Manager, Software Engineering at Capital One. We have been working on operationalizing ML for past few years at CapitalOne Bank and would like to share our experiences and lessons we learned in building an ML platform."--Resource description page